SMAD2 Mutations Are Associated with Arterial Aneurysms and Dissections. Issue 12 (10th September 2015) - Micha, Dimitra; Guo, Dong‐chuan; Hilhorst‐Hofstee, Yvonne; van Kooten, Fop; Atmaja, Dian; Overwater, Eline; Cayami, Ferdy K.; Regalado, Ellen S.; van Uffelen, René; Venselaar, Hanka; Faradz, Sultana M.H.; Vriend, Gerrit; et al.
Abstract : SMAD2 should be added to the panel of genes that are analyzed in case of arterial aneurysms and dissections with suspicion of a hereditary cause. ABSTRACT: We report three families with arterial aneurysms and dissections in which variants predicted to be pathogenic were identified in SMAD2 . Moreover, one variant occurred de novo in a proband with unaffected parents. SMAD2 is a strong candidate gene for arterial aneurysms and dissections given its role in the TGF‐β signaling pathway. Furthermore, although SMAD2 and SMAD3 probably have functionally distinct roles in cell signaling, they are structurally very similar. Our findings indicate that SMAD2 mutations are associated with arterial aneurysms and dissections and are in accordance with the observation that patients with pathogenic variants in genes encoding proteins involved in the TGF‐β signaling pathway exhibit arterial aneurysms and dissections as key features